2023
DOI: 10.3390/biology12070995
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Endothelial HIF2α/ARNT Expression for Ischemic Heart Disease Therapy

Abstract: Ischemic heart disease (IHD) is a major cause of mortality and morbidity worldwide, with novel therapeutic strategies urgently needed. Endothelial dysfunction is a hallmark of IHD, contributing to its development and progression. Hypoxia-inducible factors (HIFs) are transcription factors activated in response to low oxygen levels, playing crucial roles in various pathophysiological processes related to cardiovascular diseases. Among the HIF isoforms, HIF2α is predominantly expressed in cardiac vascular endothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 108 publications
0
2
0
Order By: Relevance
“…HIF-1α and HIF-2α recognise and bind hypoxia response elements to activate the cellular response to hypoxia. However, HIF-1α and HIF-2α have different structures and expression patterns ( 40 42 ). In this study, HIF-2α displayed different expression levels and distribution in hepatic tissue from both patients with NASH and mouse models for NASH subjected to persistent hypoxia, compared with those of HIF-1α.…”
Section: Discussionmentioning
confidence: 99%
“…HIF-1α and HIF-2α recognise and bind hypoxia response elements to activate the cellular response to hypoxia. However, HIF-1α and HIF-2α have different structures and expression patterns ( 40 42 ). In this study, HIF-2α displayed different expression levels and distribution in hepatic tissue from both patients with NASH and mouse models for NASH subjected to persistent hypoxia, compared with those of HIF-1α.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that manganese porphyrin improved survival, neurologic function recovery, and behavioral performance in animals suffering from cardiac arrest. Ullah et al [4] reviewed the current understanding of HIF2α and ARNT signaling in endothelial cells, their roles in inflammation and maintaining blood vessel integrity, and their involvement in ischemic heart disease. The two studies either provided new therapeutics for cardiac arrest or systematically reviewed the role of the HIF2α and ARNT signaling pathway in endothelial cells, which are helpful for establishing new therapeutics and targets for the development of new treatments for heart failure.…”
mentioning
confidence: 99%